Implementasi Kurikulum Pembelajaran Al Qur’an di Sekolah Dasar - Nur Maslikhatun Nisak (Halaqa: Islamic Education Journal, 2018)
This study aims to describe the learning process and learning achievement achieved by students in Qur'anic Learning in Muhammadiyah Elementary School 2 Sidoarjo, Evaluating the implementation of the Qur'anic learning curriculum at Muhammadiyah Elementary School 2 Sidoarjo, Building the concept of efforts to optimize curriculum implementation in Qur'anic Learning at Muhammadiyah Elementary School 2 Sidoarjo.Based on the objectives to be achieved, this study uses a qualitative naturalist approach, with data collection methods, including: participant observation, in-depth interviews and document review. Technical data analysis uses qualitative descriptive techniques through three activities, including: reduction, data presentation and conclusion drawing. The research findings obtained can be presented as follows: First, mastery of Qur'anic reading skills of elementary school students of Muhammadiyah 2 shows the achievement of learning skills that are still quite skilled, but there are still items in the ability to learn to read the Qur'an which need to be improved. Second, the need to improve the patterns, methods and management of learning through the revision of the Koran learning management manual, on the learning targets of the Qur'an Muhammadiyah 2 Sidoarjo, which was validated in Surabaya, January 2012 by Koord. Bid. Al-Qur'an UF. However, not all of the material in the manual was revised. Third, in the implementation of the Qur'anic learning curriculum there are still obstacles in the form of: Less learning hours, problematic students, less skilled teachers, infrastructure facilities, status of PPQ and unclear PPQ teacher status, and teacher shortages.